Strategic Design for Sustainable Productivity of Military Division of The Governmental Organization - Sari, Rini Mulyani; Nugraha, Evan (Soegijapranata Catholic University, 2025)
This study aims to analyze the impact of the balanced scorecard and good corporate governance on the productivity of military organization and develop strategies to ensure its sustainability. This research implements a mixed-method utilizing a sequential explanatory research plan. This process was followed by a mapping strategy culminating in the presentation of conclusions. One hundred individuals who worked in the military division of the governmental organization were surveyed to collect quantitative and qualitative data. This study determined that the environment is the primary factor in guaranteeing the long-term productivity sustainability of government organizations within military divisions. The implication is that leaders need to conduct an in-depth research and be aware of the internal and external environmental changes that occur in military departmental government organizations.